Recurrence of a Pheochromocytoma With TNEM127 Mutation Negative on 18F-FDOPA and 18F-FDG but Positive on 123I-MIBG and 68Ga-DOTATOC Imaging. (10th March 2022) - Cottereau, Anne-Ségolène; Garcia, Cyril; Dousset, Bertrand; Libe, Rossella; Tenenbaum, Florence
Abstract: We report the case of a 75-year-old woman with liver metastasis as a recurrence of a pheochromocytoma resected 10 years ago, with a rare germline mutation in transmembrane protein 127, falsely negative on 18 F-FDOPA and 18 F-FDG PET/CT scans but strongly positive on 123 I-MIBG scintigraphy and on 68 Ga-DOTATOC PET/CT. Functional imaging has a key role in diagnosis of pheochromocytoma and paraganglioma, especially 18 F-FDOPA shows very high sensitivity and specificity. However, 18 F-FDOPA might be falsely negative in some of these tumors, depending on specific mutations, and thus MIBG or 68 Ga-DOTATOC imaging could be an alternative.